2023
DOI: 10.3390/ani13182845
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Efficacy of Purified Quillaja Saponin Extracts in Protecting against Piscirickettsia salmonis Infections in Atlantic Salmon (Salmo salar)

Hernán Cortés,
Mario Castillo-Ruiz,
Hernán Cañon-Jones
et al.

Abstract: Piscirickettsiosis, the main infectious disease affecting salmon farming in Chile, still has no efficient control measures. Piscirickettsia salmonis is a facultative intracellular bacterium that can survive and replicate within the host macrophages, evading the immune response. Triterpenic saponins obtained from the Quillaja saponaria tree have been widely studied, and have been shown to be immunomodulatory agents, suitable for feed and vaccine applications for veterinary and human uses. The impact of the oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…These actions stimulate innate and adaptive immune responses, encompassing cellular and humoral immunity. Mechanistically, these protective effects observed in these studies were correlated to the early activation of INF-II and effector proteins like the C3 complement factor and CD8+ T cells, creating a protective microenvironment versus P. salmonis [5]. Other mechanisms might trigger the NF-kβ pathway and initiation of a pro-inflammatory transcriptional response [11].…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…These actions stimulate innate and adaptive immune responses, encompassing cellular and humoral immunity. Mechanistically, these protective effects observed in these studies were correlated to the early activation of INF-II and effector proteins like the C3 complement factor and CD8+ T cells, creating a protective microenvironment versus P. salmonis [5]. Other mechanisms might trigger the NF-kβ pathway and initiation of a pro-inflammatory transcriptional response [11].…”
Section: Introductionmentioning
confidence: 74%
“…P. salmonis can endure and proliferate within host macrophages, monocytes, and non-lymphoid cells, effectively circumventing the immune response [3,5]. In vivo and in vitro findings indicated that P. salmonis persisted for ≥120 h or more in macrophageenriched cell cultures derived from Atlantic salmon, with a concurrent peak in identifying the 16S rDNA copy number per cell [18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations